The Economics of Planting New Citrus Groves in Florida in the Era of HLB - Ariel Singerman; Marina Burani-Arouca; Stephen Hubbard Futch (EDIS)
Citrus greening, or huanglongbing (HLB), is a bacterial disease that affects citrus trees’ vascular systems, limiting nutrient uptake. As trees become increasingly affected by the disease, they suffer premature fruit drop, the fruit harvested is smaller and misshapen, and the juice quality is compromised, all resulting in lower yield. To this date there is no cure or successful management strategy to deal with HLB. This 8-page fact sheet written by Ariel Singerman, Marina Burani-Arouca, and Stephen H. Futch and published by the UF/IFAS Food and Resource Economics Department summarizes the results of an analysis of three tree densities under different production and market conditions to determine which density is most profitable. http://edis.ifas.ufl.edu/fe1050